Crosstalk between Caveolin-1/Extracellular Signal-regulated Kinase (ERK) and β-Catenin Survival Pathways in Osteocyte Mechanotransduction - Gortazar, Arancha R. (American Society for Biochemistry and Molecular Biology, 2013)
Osteocyte viability is a critical determinant of bone strength and is promoted by both mechanical stimulation and activation of the Wnt signaling pathway. Earlier studies demonstrated that both stimuli promote survival of osteocytes by activating the ERKs. Here, we show that there is interaction between the caveolin-1/ERK and Wnt/β-catenin signaling pathways in the transduction of mechanical cues into osteocyte survival. Thus, ERK nuclear translocation and anti-apoptosis induced by mechanical stimulation are abolished by the Wnt antagonist Dkk1 and the β-catenin degradation stimulator Axin2. Conversely, GSK3β phosphorylation and β-catenin accumulation induced by mechanical stimulation are abolished by either pharmacologic inhibition of ERKs or silencing caveolin-1. In contrast, the canonical Wnt signaling inhibitor dominant-negative T cell factor does not alter ERK nuclear translocation or survival induced by mechanical stimulation. These findings demonstrate that β-catenin accumulation is an essential component of the mechanotransduction machinery in osteocytes, albeit β-catenin/T cell factor-mediated transcription is not required. The simultaneous requirement of β-catenin for ERK activation and of ERK activation for β-catenin accumulation suggests a bidirectional crosstalk between the caveolin-1/ERK and Wnt/β-catenin pathways in mechanotransduction leading to osteocyte survival.